Analisis Perlindungan Hukum terhadap Penyimpangan Artificial Intelligence dalam Tindak Pidana Deepfake Pornografi Berdasarkan Hukum Pidana - Maria Karunia Putri Maan; Heryanto Amalo; Ngongo Dede (Pusat Riset dan Inovasi Nasional, 2025)
The development of digital technology based on Artificial Intelligence (AI) has had a significant impact on society, including the emergence of new crimes such as deepfake pornography. Deepfake pornography is a form of AI misuse that creates fake pornographic content by manipulating a person's face into a video or image without consent. This phenomenon raises complex legal issues within the Indonesian criminal law system. This study aims to examine how Indonesian criminal law regulates AI deviations in the form of deepfake pornography and to assess the effectiveness of these regulations in providing legal protection. This research uses a normative approach with qualitative analysis methods and the theory of legal effectiveness as the analytical tool. The research findings indicate that AI deviations in the form of deepfake pornography are not specifically regulated in Indonesia's positive criminal law. The applicable regulations are still general in nature, scattered across several laws such as the Electronic Information and Transactions Law (ITE Law), Personal Data Protection Law, Pornography Law, Sexual Violence Criminal Act Law, Copyright Law, and the Criminal Code (KUHP), which do not comprehensively address the technological aspects and psychosocial impacts of this crime. Based on Soerjono Soekanto's theory of legal effectiveness, the existing regulations are not yet effective, as seen from the legal substance, law enforcement, legal facilities and infrastructure, community factors, and legal culture. Therefore, a responsive legal reform is needed to keep pace with digital technological developments, along with strengthening the capacity of law enforcement institutions.